P‐129: Zero‐Stress Thin‐film Encapsulation Method for Increasing the Intrinsic Stability of Flexible OLEDs. Issue 1 (2nd June 2017) - Jeong, Eun Gyo; Lim, Myung Sub; Choi, Kyung Cheol
Abstract : A zero‐stress thin‐film encapsulation method was developed to mitigate residual stress. By keeping total residual stress at a minimum, the intrinsic mechanical stability of the encapsulated device was increased. The lifetimes of FOLEDs using the zero‐stress encapsulation method were increased by more than 35% compared with conventional encapsulation.